Clinical nurse’s knowledge, attitude, and practice regarding the Intrinsic Capacity of the aged: A cross-sectional study - Yi Ren; Xiumin Zhang (PLoS ONE, 2026)
Background Within the context of Chinese healthcare settings, from the perspective of clinical nursing practice in China, the present study was designed to systematically evaluate registered nurses’ theoretical knowledge, attitude, and practice(KAP)toward assessing the Intrinsic Capacity in the aging population. Methods This cross-sectional study based on online questionnaires included 606 clinical nurses who were employed in a tertiary hospital in Xinjiang from November 21, 2024 to February 18, 2025. Using the Delphi method to create a self-made online questionnaire to collect participants’ sociodemographic information and KAP scores of changes in the Intrinsic Capacity of the elderly. Results Of the collected data, 606 questionnaires were deemed valid for analysis. the research instrument showed high reliability, as evidenced by Cronbach’s α values of 0.979 for knowledge, 0.916 for attitude, and 0.936 for practice sections. Exploratory factor analysis was conducted, and the Bartlett’s test of sphericity result was 0.814.The mean knowledge score was 34.75 ± 11.165(possible range:18–90).The mean attitude score was 20.86 ± 5.488(possible range: 11–35).The mean practice score was 32.69 ± 8.695(possible range:16–72). Knowledge, attitude, and practice (KAP) scores of clinical nurses regarding the intrinsic capacity of older patients were treated as dependent variables. LASSO regression was employed to identify significant predictors. The results indicated that: nursing hierarchy ( λ = 0.509), prior receipt of intrinsic capacity training ( λ = 1.739), hospital support for new technology development in geriatric care ( λ = 2.919), and nurses’ perceived adequacy of existing knowledge to meet clinical needs ( λ = 4.755) were independently associated with knowledge scores. For attitude scores, significant predictors included hospital support for new technology development in geriatric care ( λ = 1.846), perceived adequacy of existing knowledge to meet clinical needs ( λ = 1.580), and expected frequency of training ( λ = 0.699). Practice scores were independently associated with prior receipt of intrinsic capacity training ( λ = 1.914), hospital support for new technology development in geriatric care ( λ = 0.144), the proportion of patients aged over 60 cared for during the past year ( λ = 1.176), and perceived adequacy of existing knowledge to meet clinical needs ( λ = 2.696). The structural equation modeling path coefficients revealed significant direct pathways: from knowledge to attitude( r = 0.732, P < 0.01), knowledge to practice( r = 0.617, P < 0.01), and attitude to practice( r = 0.666, P < 0.01).The bootstrap mediation effect test results indicated an indirect effect ( B = 0.421, 95%CI : 0.296–0.558) and a direct effect ( B = 0.295, 95%CI : 0.146–0.451), with effect proportions of 59% and 41%, respectively. Conclusion This investigation reveals the insufficient understanding, attitude, and practice of clinical nurses in Xinjiang towards changes in the Intrinsic Capacity of elderly patients.